APC mutations are sufficient for the growth of early colorectal adenomas. - Lamlum, H; Papadopoulou, A; Ilyas, M; Rowan, A; Gillet, C; Hanby, A; Talbot, I; Bodmer, W; Tomlinson, I (2000)
It is not clear whether APC mutations are sufficient for early colorectal adenomas to grow or whether additional mutations at other loci are required. We previously have screened 210 early colorectal adenomas from familial adenomatous polyposis patients for mutations and allelic loss at APC. Here, we determined whether allelic loss at APC had any effect on the nearby alpha-catenin gene. However, loss on 5q in familial adenomatous polyposis adenomas rarely extended as far as alpha-catenin, and no differences in alpha-catenin protein expression were found in tumors that showed loss encompassing both APC and alpha-catenin. We then screened all 210 tumors for mutations at candidate loci other than APC (K-ras, beta-catenin, and allelic loss at 1p33-p35 and 1p36) and for microsatellite instability (MSI). Each of these loci has been implicated previously in early colorectal tumorigenesis. One tumor harbored a beta-catenin mutation and another MSI, but none showed K-ras mutation or allelic loss at 1p33-p35 or 1p36. These data support the following hypotheses derived from sporadic colorectal tumors: beta-catenin mutations are generally an alternative to mutations at APC, MSI is not usually an early phenomenon in colorectal tumorigenesis, and K-ras mutations are more typical of large- and moderate-sized adenomas. Contrary to some previous reports, chromosome 1p allelic loss is infrequent in very early adenomas. APC mutations are generally sufficient for colorectal tumors to grow to about 1-cm diameter, although chance mutations at other loci can provide these early colorectal adenomas with a selective advantage, and some colorectal tumors may develop along a pathway not involving APC.